New Concept of PQR-Coordinate on Power Transformation for Harmonics Reducing - Indriarto Yuniantoro; Rudy Setiabudy; Ridwan Gunawan (Institut Teknologi Sepuluh Nopember, 2014)
Power transformation of pqr-coordinate modified by Euler angle rotation method used in analysis of the IGBT active filter circuits as the instantaneous power theory is reviewed. Twice and three times rotation of Euler angle already conducted and produced a matrix transformation different from the Kim-Akagi’s model. Method of Fourier integral in the Voltage Source PWM Converter be done so a harmonics characteristic can be known and may be reduced. Value of Euler angles in frequency domain determined as a carrier harmonic waveforms. This approach is gives slightly different than that has understood so far.